Ethnobotany Study of Medicinal Plants by the Mbojo Tribe Community in Ndano Village at the Madapangga Nature Park, Bima, West Nusa Tenggara - Novi Ani; Kurniasih Sukenti; Evy Aryanti; Immy Suci Rohyani (Jurnal Biologi Tropis, 2021)
One of the cultural characteristics of people in developing countries is that traditional elements are still dominant in everyday life. These activities include the use of plants as medicinal ingredients by various ethnic groups or groups of people living in rural areas, one of which is the Mbojo Tribe, Ndano Village in Madapangga, Bima Regency, NTB. This study aims to identify the types of medicinal plants and to describe the local wisdom of the Mbojo Tribe in Ndano Village regarding the use of medicinal plants around the Madapangga Nature Tourism Park (TWA). The results of this study are expected to contribute to the development of medicinal plant research based on local wisdom for the sustainable management of TWA Madapangga. This research is descriptive exploratory. Data collection techniques in the field by means of observation, interviews and documentation. Selection of informants for interviews using purposive sampling and snowball sampling methods. Qualitative and quantitative data were analyzed descriptively related to the aspects that have been determined. The results obtained 26 species of medicinal plants that are best known and often used by the Mbojo Tribe, Ndano Village. Utilization of this medicinal plant is used to cure diseases which amount to 31 types of diseases. Based on the habitus group, the tree level is the most widely used as medicine. Meanwhile, the part (organ) of the plant that is most widely used is the leaf. The people of Ndano Village still use a simple way of concocting medicinal plants, namely by mashing (mashed, grated, kneaded) and boiled. The use of drugs, generally done by drinking, smeared and dripped. The results of this study are very useful for the development of medicinal plant research based on local wisdom for the sustainable management of TWA Madapangga.